2020
DOI: 10.3390/w12030735
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Water Quality in Ialomita River Basin in Relationship with Land Cover Patterns

Abstract: The paper reviews the state of water quality in Ialomita River Basin (IRB), Romania, between 2007 and 2018 using the land use/land cover and basin-specific conditions effects on sediments and nutrients load. On-site monitoring was performed in two control sections of the Ialomita River, one in the upper part of the basin (near Targoviste city) and the second near the discharge into the Danube (downstream of Tandarei town). The statistical averages of water parameters for 10 years' monitoring in the control sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 38 publications
0
17
1
4
Order By: Relevance
“…Wu and Lu also reported that relief affects land use through insolation, heat, water resources, soil retention capability, and soil structure, thereby affecting the spatial distributions of pollution sources. The composition of the landform mainly affects the speed, direction of flow, and diffusion of pollutants [42,[47][48][49]. In this study, the forested areas and the spatial distribution of water quality had a negative relation, which is different from what previous studies have found.…”
Section: Discussioncontrasting
confidence: 93%
“…Wu and Lu also reported that relief affects land use through insolation, heat, water resources, soil retention capability, and soil structure, thereby affecting the spatial distributions of pollution sources. The composition of the landform mainly affects the speed, direction of flow, and diffusion of pollutants [42,[47][48][49]. In this study, the forested areas and the spatial distribution of water quality had a negative relation, which is different from what previous studies have found.…”
Section: Discussioncontrasting
confidence: 93%
“…Además, estos dos sitios son zonas de pastoreo, donde el ganado ingresa constantemente al agua y genera remoción de material, aumentando la turbidez y el aporte de materia orgánica, lo cual también se asocia con el incremento en las concentraciones de coliformes fecales y totales, que afectaron la presencia de macroinvertebrados acuáticos, registrando la abundancia y diversidad más baja (Dunea et al, 2020); por lo que las buenas prácticas agrícolas como reducir la densidad de ganado o establecer parcelas de pasto permanentes pueden reducir los fosfatos, nitratos y sólidos suspendidos en el agua. Asimismo, establecer coberturas perennes ayuda a reducir los sedimentos, permitiendo que la calidad del agua mejore y a futuro las poblaciones de macroinvertebrados también podrían mostrar una mejoría significativa (Melland et al, 2018).…”
Section: Discussionunclassified
“…Parámetros biológicos -Macroinvertebrados: La comunidad biológica depende de los nutrientes en el agua, la época, la altitud, la calidad del agua, los microhábitats, el estado de conservación del sitio, entre otros; ya que existe una relación directa entre los procesos fisiológicos de los macroinvertebrados y los parámetros fisicoquímicos del agua (Banjara et al, 2019;Medupin, 2020). De acuerdo con los resultados, la época seca presentó una mayor abundancia de macroinvertebrados acuáticos, y esto coincide con lo encontrado por Araúz, Amores y Medianero (2000), quienes afirman que, en época lluviosa, la estructura del ambiente lótico y léntico es afectada por la influencia de crecidas y se genera un efecto de arrastre sobre los macroinvertebrados acuáticos, ocurriendo una mayor abundancia de taxones cuando la precipitación es menor; además, en época lluviosa se presentó una mayor carga orgánica, a manera de turbidez que es un factor que puede generar una deflexión en la concentración de OD y a su vez puede llegar a generar una mayor carga microbiana o coliformes fecales, como se evidenció también en este estudio (Orjuela, Saldarriaga, García, & Wilches, 2010;Suárez, García, & Vaca, 2012;Goldyn et al, 2018;Windsor et al, 2019;Medupin, 2020;Dunea, et al, 2020).…”
Section: Discussionunclassified
“…Esto produce cambios fisicoquímicos y biológicos en el agua y favorece a la eutrofización. Además, incrementa la temperatura y la conductividad y ocasiona efectos adversos a los organismos acuáticos de manera permanente (Tadesse, Tsegaye, & Girma, 2018;Dunea et al, 2020).…”
Section: Discussionunclassified